Recent Studies and Progress in the Intratumoral Administration of Nano-Sized Drug Delivery Systems - Wan Su Yun; Jeongrae Kim; Dong-Kwon Lim; Dong-Hwee Kim; Seong Ik Jeon; Kwangmeyung Kim (Nanomaterials, 2023)
Over the last 30 years, diverse types of nano-sized drug delivery systems (nanoDDSs) have been intensively explored for cancer therapy, exploiting their passive tumor targetability with an enhanced permeability and retention effect. However, their systemic administration has aroused some unavoidable complications, including insufficient tumor-targeting efficiency, side effects due to their undesirable biodistribution, and carrier-associated toxicity. In this review, the recent studies and advancements in intratumoral nanoDDS administration are generally summarized. After identifying the factors to be considered to enhance the therapeutic efficacy of intratumoral nanoDDS administration, the experimental results on the application of intratumoral nanoDDS administration to various types of cancer therapies are discussed. Subsequently, the reports on clinical studies of intratumoral nanoDDS administration are addressed in short. Intratumoral nanoDDS administration is proven with its versatility to enhance the tumor-specific accumulation and retention of therapeutic agents for various therapeutic modalities. Specifically, it can improve the efficacy of therapeutic agents with poor bioavailability by increasing their intratumoral concentration, while minimizing the side effect of highly toxic agents by restricting their delivery to normal tissues. Intratumoral administration of nanoDDS is considered to expand its application area due to its potent ability to improve therapeutic effects and relieve the systemic toxicities of nanoDDSs.